Feeding and defecation behavior of Triatoma rubida (Uhler, 1894) (Hemiptera: Reduviidae) under laboratory conditions, and its potential role as a vector of chagas disease in Arizona, USA - Reisenman, Carolina Esther (2011)
Chagas disease is caused by the parasite Trypanosoma cruzi, which is transmitted to humans by blood-sucking triatomine insects. This disease is endemic throughout Mexico and Central and South America, but only a few autochthonous cases have been reported in the United States, despite the fact that infected insects readily invade houses and feed on humans. Competent vectors defecate during or shortly after feeding so that infective feces contact the host. We thus studied the feeding and defecation behaviors of the prevalent species in southern Arizona, Triatoma rubida. We found that whereas defecation during feeding was frequent in females (93%), it was very rare in immature stages (3%), and absent in males. Furthermore, more than half of the immature insects that exhibited multiple feeding bouts (62%) defecated during interruptions of feeding, i.e., while likely on or near the host. These results indicate that T. rubida potentially could transmit T. cruzi to humans.